Diversity analysis of some selected rice genotypes through SSR- based molecular markers - Shahriar, MH; Robin, AHK; Begum, SN; Hoque, A (Journal of the Bangladesh Agricultural University, 2016)
An experiment was carried out to assess the genetic diversity of advanced rice (Oryza sativa L.) breeding lines using three SSR markers viz., RM147, RM167 and RM215. Thirty T- aman advanced breeding lines at F9 generation along with 4 check varieties were assessed. All three primers showed polymorphism. A total of 29 alleles were detected among the rice genotypes with an average of 9.67 alleles per locus. Polymorphism information content (PIC) ranged from 0.47 to 0.88 with an average of 0.71. A dendrogram was constructed based on total microsatellite polymorphism and 34 genotypes were grouped into four major clusters at 0.36 similarity co-efficient differentiating the early maturing genotypes from the late maturing types. The information about the genetic diversity might be utilized in future breeding programs for developing rice varieties with much shorter growth duration. The results also suggested that microsatellite markers which are linked to genes or QTLs responsible for growth duration properties are suitable tools for marker assisted selection (MAS) to select the rice genotypes of shorter growth duration. J. Bangladesh Agril. Univ. 12(2): 307-311, December 2014